Bibliometric study on the impact of knowledge management in business - Wong-Torres, Camila (2024)
This article describes the results of a systematic review of the bibliography that seeks to identify the main impacts of knowledge management on business. For this, the research used the method of the consolidated meta-analytic approach theory (TEMAC). During the investigation, it was found that authors from China and England concentrate 47% of the publications related to the subject of study. Likewise, the findings provide strong evidence of the positive benefits of effective knowledge management in business. It is highlighted that this management is associated with the strengthening of social capital, the generation of innovation, the improvement of efficiency and organizational performance, as well as the promotion of business sustainability. Based on the above, 3 main thematic axes are identified on the impacts of knowledge management on business; the innovation; efficiency and performance; and sustainability.